Video-based versus educational booklet training on self-care performance of patients with cataract - Zarifsanaiey, Nahid; Hedayat, Maryam; Mehrabi, Manoosh; Bagheri, Zahra (Bangladesh Journal of Medical Science, 2022)
Background and Objective: Training patients can increase their knowledge and skills in self-care performance after cataract surgery. The present study compared the effect of videobased training and educational booklet methods on the self-care performance of patients with cataracts. Methods and Material: In this interventional study,83eligible patients a day prior to their cataract surgery were enrolledin the study based on the convenient sampling method conducted in 2020.Then, the patients were allocated into a video-based training group (n= 40) and educational booklet (n=43) group by the permuted block random sampling method. The patients completed a researcher-made questionnaire one day before and one day after the intervention to be assessed for their knowledge and self-care performance after cataract surgery. Face as well as content validity (CVR = 0.99, CVI = 0.8) and reliability (0.839) of the data collection tool were confirmed. For statistical analysis, independent t-test and analysis of covariance were used, using SPSS16 software. Results and Discussion: Based on the results, video-based training and educational booklet had the same effect on increasing the level of knowledge among the patients. Also, the mean score of self-care performance was significantly higher in the videobased training compared to the booklet group after the intervention (P=0.014). Conclusion: Video-based training can significantly enhance patients’knowledge and self-care performance regarding cataract than training the patients via the educational booklet. Bangladesh Journal of Medical Science Vol. 21 No. 03 July’22 Page: 601-609